2014
DOI: 10.20286/nova-jmbs-030130
|View full text |Cite
|
Sign up to set email alerts
|

Ethno-Pharmacological Survey, In Vitro Anti-Sickling and Free Radical Scavenging Activities of Carapa Procera DC. Stem Bark (Meliaceae)

Abstract: Drepanocytosis is a genetic and neglected disease, endemic in negroids population. One of the main characteristics of this pathology is the production of a large amount of free radicals, leading to a severe oxidative stress and the consumption of NO by free oxygen radicals, and/or by cell-free plasma heme. The consequences of this defect are hemolytic anemia and tissue damage brought about by the blockage of blood vessels by the sickled cells. The present study evaluated the antisickling and radical scavenging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 20 publications
1
20
0
1
Order By: Relevance
“…Chemicals derived from medicinal plants have great potential to treat many diseases and are widely investigated for diverse health issues [4,[14][15][16]. Our previous works [5,[17][18][19][20][21][22] have led to the identification of various bioactive agents against SCD from plants including betulinic acid (A), betulinic acid acetate (B), friedelan-3-one (C), and ursolic acid (E), whereas the isolated β-sitosterol (D) was found to be inactive ( Fig. 1a-e).…”
Section: Introductionmentioning
confidence: 99%
“…Chemicals derived from medicinal plants have great potential to treat many diseases and are widely investigated for diverse health issues [4,[14][15][16]. Our previous works [5,[17][18][19][20][21][22] have led to the identification of various bioactive agents against SCD from plants including betulinic acid (A), betulinic acid acetate (B), friedelan-3-one (C), and ursolic acid (E), whereas the isolated β-sitosterol (D) was found to be inactive ( Fig. 1a-e).…”
Section: Introductionmentioning
confidence: 99%
“…Surveys undertaken by our research team in DRC conducted to more than 115 medicinal plants used in Congolese traditional medicine to manage sickle cell disease among which was O. basilicum [5] [7]- [15]. In fact, in our previous works, our research team has shown that O. basilicum like some of medicinal plants used in Congolese herbal medicine in the management of sickle cell disease have antisickling activity in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of fact, the use of plants and invertebrates for therapeutic purposes is well established in great apes. Indeed, because of their phylogenetic closeness and common neural pathways of chemosensory perception, humans and great apes, when displaying symptoms of illness learn to select some biological resources as medicine [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In order to discover new effective molecules against human diseases, some researchers have been studying for several years, the self-medication behaviour in non-human primates in their natural environments in order to identify plant taxa and/or animals that they use for their treatment [8,9]. In the particular case of animal taxa, Simmen et al [10] of National Museum of Natural History of Paris (France) reported that lemurs of Madagascar use diplopods secretions to heal against various skin diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation